A little devil in America : notes in praise of black performance - Abdurraqib, Hanif, 1983- (New York : Random House, 2021)
"A Little Devil in America is an urgent project that unravels all modes and methods of black performance, in this moment when black performers are coming to terms with their value, reception, and immense impact on America. With sharp insight, humor, and heart, Abdurraqib examines how black performance happens in specific moments in time and space--midcentury Paris, the moon, or a cramped living room in Columbus, Ohio. At the outset of this project, Abdurraqib became fascinated with clips of black minstrel entertainers like William Henry Lane, better known as Master Juba. Knowing there was something more complicated and deep-seated in the history and legacy of minstrelsy, Abdurraqib uncovered questions and tensions that help to reveal how black performance pervades all areas of American society. Abdurraqib's prose is entrancing and fluid as he leads us along the links in his remarkable trains of thought. A Little Devil in America considers, critques, and praises performance in music, sports, writing, comedy, grief, games, and love"-- (Provided by publisher.)
boek
Keywords: African Americans in the performing arts; American literature -- African American authors -- History and criticism; African Americans -- Race identity; United States -- Race relations; African Americans -- Intellectual life; African Americans -- Social conditions